Kendala-kendala Sejarah dalam Penerimaan Etnis Cina di Indonesia yang Multikultural - Charles A. Coppel (Antropologi Indonesia, 2003)
Indonesia's motto (Bhinneka Tunggal Ika), like that of the United States (E pluribus unum), suggests a multicultural unity in diversity appropriate to such a large nation comprising hundreds of ethnic groups (suku bangsa). Not every ethnic group has been treated in the same way, however. Ethnic Chinese Indonesians have been classified as people of foreign descent (keturunan asing) rather than as a suku bangsa, although many peranakan Chinese families have been settled in Indonesia for centuries and have indigenous as well as Chinese ancestry. Why was itso difficult for peranakan Chinese to gain acceptance as Indonesians? Why were their counterparts, the mestizo Chinese, accepted so readily as Filipinos? The paper will consider the timing of the rise of the relevant national consciousnesses (Chinese, Filipino, Indonesian) and their interactions, as well as the policies of the relevant governments (colonial and Chinese) toward the ethnic Chinese population in the two countries. Partha Chatterjee has written about nationalist thought in the Third World as a derivative discourse. It will be argued that Indonesian nationalist thought, in its attitudes to the ethnic Chinese, has been heavily influenced by the policies and mentality of the Dutch colonial government.